2016
DOI: 10.2489/jswc.71.1.41
|View full text |Cite
|
Sign up to set email alerts
|

The ability of cover crops to reduce nitrogen and phosphorus losses from arable land in southern Scandinavia and Finland

Abstract: This review summarizes current knowledge from the literature and experimental studies on the role of cover crops (CCs) in reducing nitrogen (N) leaching and phosphorus (P) losses to waters under the marine and humid continental climate conditions of southern Scandinavia and Finland. Field leaching studies from 11 sites indicate that undersown ryegrass (Lolium spp.) CCs are robust, with average N uptake in aboveground CC biomass of 7 to 38 kg N ha -1 (6.2 to 34 lb N ac -1). Use of CCs sown at harvest (e.g., cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(105 citation statements)
references
References 82 publications
4
100
0
1
Order By: Relevance
“…In 2015, 129,095 ha of cover crops of cereal rye, oats, and radishes were planted by Illinois producers (ILEPA, 2014), with notable increases in in southern Illinois (Rundquist and Carlson, 2017). Cover crops have complex impacts on net P losses because cover crops can lead to lessened P loss via surface run‐off and leaching (Aronsson et al, 2016; Zhang et al, 2017) yet have been found to increase dissolved P losses following freeze–thaw cycles (Øgaard, 2015; Riddle and Bergstrőm, 2013) or post‐termination precipitation events (Cober et al, 2018). Conservation tillage can reduce soil erosion and thus associated risk of P loss as particulate P, which is estimated to account for the majority (≥60%) of P losses in Illinois (ILEPA, 2014).…”
Section: Illinois: a Case Study In Multidisciplinary Approaches To Rementioning
confidence: 99%
“…In 2015, 129,095 ha of cover crops of cereal rye, oats, and radishes were planted by Illinois producers (ILEPA, 2014), with notable increases in in southern Illinois (Rundquist and Carlson, 2017). Cover crops have complex impacts on net P losses because cover crops can lead to lessened P loss via surface run‐off and leaching (Aronsson et al, 2016; Zhang et al, 2017) yet have been found to increase dissolved P losses following freeze–thaw cycles (Øgaard, 2015; Riddle and Bergstrőm, 2013) or post‐termination precipitation events (Cober et al, 2018). Conservation tillage can reduce soil erosion and thus associated risk of P loss as particulate P, which is estimated to account for the majority (≥60%) of P losses in Illinois (ILEPA, 2014).…”
Section: Illinois: a Case Study In Multidisciplinary Approaches To Rementioning
confidence: 99%
“…Up to 14% of 37 the arable land may carry catch crops on farms with intense cereal production. However, national 38 regulations of N use and nitrate catch crops may differ even within regions with comparable climate 39 and production systems (Aronsson et al, 2016). 40…”
Section: Introduction 27mentioning
confidence: 99%
“…On average over 5 years (1 August‐31 July, 2013–2018), the reduction in N leaching with an oilseed radish cover crop compared with unplanted control plots was 59% (range 45%–76%). This is greater than the average reduction of 43% estimated from a number of field experiments in the Nordic region that included different species of cover crops and different times of incorporation (Aronsson et al., ). Although the growth of oilseed radish was probably somewhat constrained due to the cold climate and since it was not allowed to grow over winter, it still had a significant impact on N leaching.…”
Section: Resultsmentioning
confidence: 65%
“…On average over 5 years (1 August-31 July, 2013-2018), the reduction in N leaching with an oilseed radish cover crop compared with unplanted control plots was 59% (range 45%-76%). This is greater than the average reduction of 43% estimated from a number of field experiments in the Nordic region that included different species of cover crops and different times of incorporation (Aronsson et al, 2016).…”
Section: Drainage Watermentioning
confidence: 61%